Coarse-grained molecular dynamics study of wettability influence on protein translocation through solid nanopores. (12th February 2019) - Liu, Zhenyu; Shi, Xiaorui; Wu, Huiying
Abstract: Protein translocation through nanopores is widely involved in molecular sensing and analyzing devices, whereby nanopore surface properties are crucial. However, fundamental understanding of how these properties affect protein motion inside nanopores remains lacking. In this work, we study the influence of nanopore surface wettability on voltage-driven protein translocation through nanopores with coarse-grained molecular dynamics simulations. The results show that the electrophoretic mobility of protein translocation increases as the contact angle of nanopore surface increases from 0° to 90°, but becomes almost constant as the contact angle is above 90°. This observation can be attributed to the variation of the friction coefficient of protein translocation through the nanopores with different nanopore contact angles. We further show that the interaction between nanopore and water, rather than that between the nanopore and protein, dominates the protein transport in nanopores. These findings provide new insights into protein translocation dynamics across nanopores and will be beneficial to the design of high-efficiency nanopore devices for single molecule protein sensing.